PENGALIHAN HAK MEREK MELALUI WAKAF BERDASARKAN HUKUM POSITIF INDONESIA DAN PRINSIP SYARIAH - Yustisia, Fasya; Budiningsih, Catharina Ria (Faculty of Law, Parahyangan Catholic University, 2019)
This article discusses the utilization of the Islamic institution of wakaf (an Islamic institution) to transfer ownership or right to use of trademark. The issue at hand is that method of trademark transfer is found regulated by Law No. 20 of 2016 re. Trademark and Geographical Indication whilst procedure and conditions of wakaf is regulated by Islamic/Syariah Law (Law No. 41 of 2004). The author notes that wakaf, understood as transfer of (ownership or proprietorship) of Trademarks, is or should be motivated by religious considerations or made in the public interest. Therefore, transfer done through wakaf will always be made in perpetuity. Nonetheless, the Law no. 41 of 2004 re. wakaf make possible temporary transfer of ownership which may be performed by a license agreement, transferring only right to use the trademark but not the ownership (title) thereof. Another important note to be highlighted is that Islamic law prohibits or considers not appropriate (not halal) trademark of living being or non-kosher products (goods or services).